Heteronormativity, Intrafamilial Coexistence with Homophobic Figures (Global Journal of Human-Social Science, 2024)
According to data from the WHO-UN Comprehensive Action Plan on Mental Health Health 2022 lesbian gay bisexual transgender and intersex people represent a high rate among vulnerable and discriminated groups The mental health identified as a risk factor as well as violent acts abuse and the feeling of isolation makes it clear that living in conflict with society in general can lead to poor mental health especially in the family environment Where different behaviors are classified as erroneous and negative to the unexpected genderroles that were socially designated The objective of this project is to offer information to students of Higher-Level Schools and Faculties that impacts the well-being of those around them As well as in mental health which allows them to manage a family environment in harmony with heteronormativity related to a non-normative gender identity The methodology used corresponds to mixed research where at first there is direct interaction with the study phenomenon and work with a population recognition survey Collecting data through a Likert-type measurement survey It is concluded that bisexuality is the predominant sexual orientation followed by gay and lesbian orientation where their sexual orientation is unknown to their family with at least one homophobic family member Likewise it is concluded that the events that happen in the family have an impact on the emotional behavioral and attitudinal states of the people who make it up
Keywords: family; homophobic; violence; harassment; gender